1989
DOI: 10.1073/pnas.86.12.4715
|View full text |Cite
|
Sign up to set email alerts
|

Coamplification of human acetylcholinesterase and butyrylcholinesterase genes in blood cells: correlation with various leukemias and abnormal megakaryocytopoiesis.

Abstract: To study the yet unknown role of the ubiquitous family of cholinesterases (ChoEases) in developing blood cells, the recently isolated cDNAs encoding human acetyicholinesterase (AcChoEase; acetylcholine acetyihydrolase, EC 3.1.1.7) and butyrylcholinesterase (BtChoEase; cholinesterase; acylcholine acylhydrolase, EC 3.1.1.8) were used in blot hybridization with peripheral blood DNA from various leukemic patients. Hybridization signals (10-to 200-fold intensifled) and modified restriction patterns were observed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 38 publications
2
42
0
1
Order By: Relevance
“…By the use of specific inhibitors we demonstrated that some of the cholinesterase activity was probably due to BuChE activity, and some of it due to AChE activty. The coexpression of the two cholinestreases in one cell type is not surprising, since in other ceils of the hematopoietic system there is also coexpression of both enzyme types [20]. The detected AChE activity level was similar to that reported for leukocytes [21].…”
Section: Discussionsupporting
confidence: 84%
“…By the use of specific inhibitors we demonstrated that some of the cholinesterase activity was probably due to BuChE activity, and some of it due to AChE activty. The coexpression of the two cholinestreases in one cell type is not surprising, since in other ceils of the hematopoietic system there is also coexpression of both enzyme types [20]. The detected AChE activity level was similar to that reported for leukocytes [21].…”
Section: Discussionsupporting
confidence: 84%
“…Further analysis revealed the occurrence of coamplified ACHEDNA and CHEDNA sequences in genomic DNA from peripheral blood cells of leukemic patients (9). Altogether, these findings raised the question whether the previously reported high level of expression of the ACHE and CHE enzymes in tumors (10, 1 1) is effected by gene amplification.…”
Section: Introductionmentioning
confidence: 64%
“…In embryonic life, definition of the role of cholinesterases in cellular proliferation and differentiation have started the investigations on possible involvement of BChE and AChE in tumorogenesis. Abnormal expression of both BChE and AChE, and in vivo amplification of their genes have been observed in intracranial neoplasms such as meningioma (67), glioma (68), and acuostic neurinomas (69), lung cancers (70), megakaryocytopoietic disorders and leukemias (71), ovarian tumors (72). It is also shown that AChE and BChE modulate cell adhesion in human neuroblastoma cells (62).…”
Section: Resultsmentioning
confidence: 99%
“…It is also shown that AChE and BChE modulate cell adhesion in human neuroblastoma cells (62). Antisense blocking of BChE has been shown to result in an inhibition of megakaryocytopoiesis and application of similar techniques in embryonic chick retinal cell resulted in an inhibition of proliferation (61,71). So we will read more about the relationship between BChE and tumorogenesis and the usage of specific BChE inhibitors used as chemothreapeutic agents in the future also.…”
Section: Resultsmentioning
confidence: 99%